Serotype Composition of Streptococcus pneumoniae In Children With Respiratory Infections, Optimization of Molecular Assessment Methods - E. V. Nikitina; I. A. Tsvetkova; O. S. Kalinogorskaya; V. V. Gostev; S. S. Belanov; A. S. Mokhov; E. L. Kalisnikova; D. P. Gladin; V. A. Ageevets; S. V. Sidorenko (Антибиотики и Химиотерапия)
.